تقييم نتائج علاج التهاب البلعوم المزمن - يوسف يوسف; الرستم محمد; داؤد سامر (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة إلى معرفة أفضل السبل في علاج مرضى التهاب البلعوم المزمن, وذلك بالاعتماد على الأعراض التي اشتكى منها المرضى قبل العلاج وبعده, وكذلك بالاعتماد على معطيات الفحص السريري. وقد تكونت مادة البحث من 100 مريض من مراجعي العيادة الأذنية والوحدة المهنية لأمراض الأذن والأنف والحنجرة في مشفى الأسد الجامعي ممن شخص لهم التهاب بلعوم مزمن, وذلك بين عامي (2003-2005). حيث تم تقسيم هؤلاء المرضى إلى ثلاث مجموعات: 1- المجموعة الأولى: تألفت من 25 مريضا عولجوا معالجة دوائية. 2- المجموعة الثانية: تألفت من 31 مريضا عولجوا معالجة خاصة بضبط الأمراض العامة المرافقة 3- المجموعة الثالثة: تألفت من 44 مريضا عولجوا معالجة فيزيائية بالأشعة فوق البنفسجية. وقد تمت مراقبة هؤلاء المرضى لمدة عام بعد المعالجة, وقد قمنا بتقييم نتائج العلاج على الشكل التالي: 1-التحسن الجيد:تراجعت فيه كل شكاوى المريض. 2- التحسن الوسط: تراجعت فيه بعض الأعراض وبقيت أعراض أخرى. 3- عدم التحسن: لم يحدث فيه أي تراجع للأعراض السريرية. وقد تم الحصول على النتائج التالية: عند المجموعة الأولى: التحسن الجيد : 33.3%, التحسن الوسط: 26.6%, عدم التحسن: 40% عند المجموعة الثانية: عند مرضى السكري : وقد كان عددهم 15 مريض التحسن الجيد : 14.2%, التحسن الوسط:28.57%, عدم التحسن : 57.14% عند مرضى القلس المعدي المريئي : وقد كان عددهم 10 مرضى التحسن الجيد: 40%, التحسن الوسط: 40%, عدم التحسن :20% عند مرضى فقر الدم بعوز الحديد : وقد كان عددهم 6 مرضى التحسن الجيد : 83.3%, التحسن الوسط: 16.6%, عدم التحسن : 0 % عند المجموعة الثالثة: التحسن الجيد : 61.36%, التحسن الوسط : 20.45%, عدم التحسن :18.18% مما سبق نستنتج أن أفضل النتائج 61.36% كانت عند المرضى الذين عولجوا فيزيائيا بالأشعة فوق البنفسجية, كذلك كانت النتائج أفضل عند مجموعات المرضى الذين عولجوا إضافة للمعالجة الخاصة بالأشعة فوق البنفسجية . The aim of this study was to know the best methods in treatment of patients with chronic pharyngitis depending on symptoms which the patients complained before and after treatment, depending on the findings in clinical examination . The study includes 100 patients from E.N.T outpatient clinic in Al-Assad University Hospital – Lattakia between 2003-2005, who complained of chronic pharyngitis in different type and causes. Patients were classified into 3 groups: 1-first group: consists of 25 patients, who were treated by medical therapy . 2-second group: consists of 31patients, who were treated by special therapy by control the associated general diseases. 3-third group: consist of 44 patients, who were treated by physical therapy with ultra-violet rays. After 1 year of observation post therapy ,we assess the treatment results as following: 1-good improvement: patient’s complaints decreased. 2-intermediate improvement: some of the patient’s complaints decreased and others did not. 3-no improvement: no regression of patients complaints. we reached to the following results : in the first group : the good improvement was 33.3%, the intermediate improvement was 26.6% and no improvement was 40% in the second group : a-diabetic patients15cases the good improvement was 14.2%, the intermediate improvement was 28.57% and no improvement was 57.14% b-patients with gastro esophageal reflux10cases the good improvement was 40%, the intermediate improvement was 40% and no improvement was 20% c-patients with iron deficiency anemia 6cases: the good improvement was 83.3%, the intermediate improvement was 16.6%, no improvement was 0%. in the third group : the good improvement was 61.36% the intermediate improvement was 20.45% no improvement was 18.18% So the best results were 61.36% in physically treatment patients by ultra-violet rays. the results were also better in the group which treated by special therapy in addition to ultra-violte rays.